Selenite and Selenate Effects on Mercury (Hg2+) Uptake and Distribution in Tilapia, Oreochromis niloticus L., Assessed by Chronic Bioassay - Carvalho, G. G. A.; de Franca, J. G. [UNESP]; Dias, D. C. [UNESP]; Lombardi, J. V.; de Paiva, M. J. R.; Carvalho, S. [UNESP]; Sarries, G. A.; Ferreira, J. R. (Springer, 2009)
Aquatic organisms are considered excellent biomarkers of mercury (Hg) occurrence in the environment. Selenium (Se) acts in antagonism to this metal, stimulating its elimination, and reducing its toxicity. In this paper, tilapia (Oreochromis niloticus) were chronically acclimated in sub-lethal Hg2+, Hg2+ + Se4+ and Hg2+ + Se6+ concentrations. Distribution and bioaccumulation of both elements were evaluated in fish tissues. The kidney was the main target of the Hg and Se uptake, and the presence of Hg induced the Se hepatic elimination. The Hg bioaccumulation in the gill, spleen and heart were higher in the presence of Se6+ than in the presence of Se4+.
Keywords: Mercury; Selenium; Fish; Chronic toxicity